Mapping the routes and staging points of cross-border crime in the eastern Sabah security zone (ess zone), Malaysia, 2000-2023 - B.B.B. Bee; N. Sakke; I. Ramli; R. Dollah; A. Jafar; E.P. Joko; H. Jovita (ResearchGate, 2025)
The threat of cross-border crime (CBC) in the Sulu-Celebes sea is a persistent challenge, particularly along the eastern coast of Sabah, where it poses a significant risk to regional security. This paper advocates for the use of Geographic Information System (GIS) tools to visually represent and analyze the dynamics of CBC in the region. GIS mapping identifies five primary focal areas and 14 distinct routes that are critical to understanding the movement of illicit activities in the Eastern Sabah Security Zone (ESS Zone). Notably, high incident point such as the Sibutu/Sitangkau-Semporna and Sibutu/Sitangkai/Omapui-Kunak/Lahad Datu corridors account for 10 key CBC routes. Further analysis reveals approximately four additional major routes in areas like Bongao/Sibutu–Kinabatangan, Taganak/Bakungan–Sandakan and Mangsi–Kudat. Over two decades between 2000-2022, these maritime routes have been pivotal in facilitating CBC activities in Sabah's waters. This visual mapping provides valuable insights for security forces, empowering them to adopt proactive strategies to combat CBC. It aims to enhance understanding of geographical patterns and criminal tactics, informing strategic interventions to prevent and mitigate the threats of CBC in the region, thus contributing to broader regional security efforts.